Preparation and characterization of slow-release of pineapple leaf-graft-polyacrylamide superabsorbent polymer - Norsakinah Adanan, 1989-, author; Shahrir Hashim, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper (Sarjana Muda Kejuruteraan (Kimia - Polimer)) - Universiti Teknologi Malaysia, 2012